Penyuluhan Tentang Massage Efflurage Sebagai Solusi Tepat Dalam Mengurangi Nyeri Persalinan - Nurul hidayah bohari; Haerani rani; husnul Khatimah; Kurniati Akhfar (JCS, 2022)
Normal delivery occurs at term and runs spontaneously at the beginning with the fetus showing the head as the front end (Vertex Presentation), the process ends within 18 hours without any complications. The birth process is the process of opening and thinning the cervix and the fetus descends into the birth canal. Labor and birth are said to be normal if the expulsion process that occurs at full term of pregnancy (37-42 weeks), is born spontaneously with a back of the head presentation, is not accompanied by complications for both the mother and the fetus. Massage or massage during labor can have a relaxing effect. Relaxation experienced by the mother stimulates the brain to reduce levels of the hormone adrenaline and increase the production of oxytocin, which is an important factor in the emergence of adequate contractions. Massage technique is an instinctive aspect of humans when they feel pain in several parts of the body and this technique creates the first reaction, which is to spread the sore body parts with their hands to reduce pain. This massage aims to increase blood circulation, apply pressure, and warm up the abdominal muscles and promote physical and mental The counseling material consists of the definition of message effleurage, the benefits of message effleurage.